Reseña de Joseph Frankel, International Relations in a Changing World - Rojas, María Eugenia (Revista Mexicana de Política Exterior, 1984)
Joseph Frankel, International Relations in a Changing World, Oxford, Oxford University Press, 1983, 218 pp.